The Use Of Spelling Bee Game To Improve Students’ Vocabulary - Asri Syarifuddin; Husnani Aliah; Syahrir (Jurnal Serambi Ilmu, 2024)
The research entitled “The Use of Spelling Bee to Improve Students` Vocabulary” discovers the effectiveness of the use of Spelling Bee in teaching vocabulary using Spelling Bee game. This research was using pre-experimental design. Pre-experimental design is the simplest research model that uses one to several groups by giving certain treatments and being observed so that changes occur. The research utilized one-group pre-test and post-test. The research location was held at SMPN 5 Palopo, the respondents in the study were eighth grade students namely eighth A and eighth B by used cluster random sampling. The method used in collecting data is pre-test with post-test. The data from the post-test are analyzed statistically using SPSS 25 for Windows. The result of paired sample test showed the result of the analytical comparisons using t-test. The output shows the average before and after the test (-30,000), standard deviation (10,310), mean standard error (2,305). The bottom difference (-41.825), while the top difference (-32,174). The result of the t test = (-16,048) with a df of 19 and a significance of 0,000. Mean score where higher after teaching using Spelling bee games. In conclusion, the use of Spelling be games is an effective strategy that will use to teach class VIII students of SMPN 5 Palopo.